Expression of IL‐34 correlates with macrophage infiltration and prognosis of diffuse large B‐cell lymphoma. Issue 8 (13th August 2019) - Noyori, Osamu; Komohara, Yoshihiro; Nasser, Hesham; Hiyoshi, Masateru; Ma, Chaoya; Pan, Cheng; Carreras, Joaquim; Nakamura, Naoya; Sato, Ai; Ando, Kiyoshi; Okuno, Yutaka; Nosaka, Kisato; et al.
Abstract: Objectives: Infiltration of macrophages through the tyrosine kinase receptor CSF1R is a poor prognosis factor in various solid tumors. Indeed, these tumors produce CSF1R ligand, macrophage colony‐stimulating factor (M‐CSF) or interleukin‐34 (IL‐34). However, the significance of these cytokines, particularly, the newly discovered IL‐34 in haematological malignancies, is not fully understood. We therefore analysed the role of IL‐34 in diffuse large B‐cell lymphoma (DLBCL), the most common subtype of malignant lymphoma. Methods: We analysed formalin‐fixed paraffin‐embedded lymphoma tissues of 135 DLBCL patients for the expression of IL‐34 and the number of macrophages, and the survival of these patients. The expression of IL‐34 in DLBCL cell lines and the activity of IL‐34 to induce the migration of monocytic cells were also characterised. Results: Several lymphoma tissues showed a clear IL‐34 signal, and such signal was detectable in 36% of patients. DLBCL cell lines also expressed IL‐34. Interestingly, the percentage of IL‐34 + patients in the activated B‐cell subtype was significantly higher than that in the germinal centre B‐cell subtype. More interestingly, IL‐34 + patients showed shorter survival periods and higher number of macrophages in lymphoma tissues. The recruitment of monocytes is likely the first step for the higher macrophage density in the IL‐34 + lymphoma tissues. Indeed, IL‐34 induced the migration of monocytic cells. Conclusion: Our results raise the possibility that IL‐34 in lymphoma tissues of DLBCL patients recruits monocytes, leading to the higher number of macrophages in the tissues and poor prognosis of patients. IL‐34 may be an additional therapeutic target of DLBCL. Abstract : Diffuse large B‐cell lymphoma (DLBCL) is the most common subtype of malignant lymphoma. Here, we demonstrate that IL‐34, which induces the migration of monocytes and differentiation into macrophages, is expressed in lymphoma tissues of DLBCL, which correlates with the higher number of macrophages in the tissues and poor prognosis of patients.